HUBUNGAN RESISTENSI INSULIN DENGAN KADAR NITRIC OXIDE PADA OBESITAS ABDOMINAL - Cahjono, Heru; Gde Budhiarta, Anak Agung (journal of internal medicine, 2007)
Numerous studies that confirmed the important link between central obesity and endothelial dysfunction (ED) is furthersupported by the concept that insulin sensitivity is partly determined by the ability of endothelium to produce nitric oxide (NO).In this condition, HOMA-IR, the model which is a convenient means of evaluating insulin resistance has thus far been related toED. Nitric oxide plays important physiological roles in the endothelium, where free radical NO is synthesized from the aminoacid l-arginine by endothelial constitutive NO synthase (eNOS) and released. Endothelium-derived NO is a potent vasodilator aswell as an inhibitor of platelet aggregation and adhesion, and is associated with the development of cardiovascular disease (CVD)in the presence of endothelial dysfunction (ED), which plays an early and prominent role in atherosclerotic plaque formation. Weraised the question as to whether insulin resistance in the abdominal obesity group had association with NO levels contribute toaffect endothelial dysfuntion. Cross sectional study had been conducted during January until March 2007. The study involved 67employees at Sanglah Hospital with abdominal obesity using criteria for Asian people (male WC 90 cm; female WC 80 cm).Serum concentrations of NO metabolites were evaluated through the measurement of metabolic end products, ie, nitrite andnitrate, using enzymatic catalysis coupled with Griess reaction, Serum concentration of insulin was measured by immunoassaymethod. Plasma glucose, cholesterol, HDL-cholesterol, LDL-cholesterol and triglicerydes were determined by enzymatic procedureafter overnight fast. The study involved 45 female and 25 male subjects, 23-56 years of age. Insulin resistance had associationwith waist circumference (r=0,511; p <0,01) and there was no association between insulin resistance and NO titer (r=0,054;p<0,664) but after adjusted with ESR 20-30 mm/h r=-0,486; p<0,048. However, serum concentrations of NO did not have associationwith component of metabolic syndrome and neither did insulin resistance. The present data indicate there is no associationbetween insulin resistance and NO levels except for ESR 20-30 mm/h. This possibility is due to low grade chronic inflammationrole on the pathogenesis of endothelial dysfunction in obesity